Three-Dimensional Numerical Modeling of Ground Ice Ablation in a Retrogressive Thaw Slump and Its Hydrological Ecosystem Response on the Qinghai-Tibet Plateau, China - Fujun Niu; Chenglong Jiao; Jing Luo; Junlin He; Peifeng He (International Journal of Disaster Risk Science, 2023)
Abstract Retrogressive thaw slumps (RTSs), which frequently occur in permafrost regions of the Qinghai-Tibet Plateau (QTP), China, can cause significant damage to the local surface, resulting in material losses and posing a threat to infrastructure and ecosystems in the region. However, quantitative assessment of ground ice ablation and hydrological ecosystem response was limited due to a lack of understanding of the complex hydro-thermal process during RTS development. In this study, we developed a three-dimensional hydro-thermal coupled numerical model of a RTS in the permafrost terrain at the Beilu River Basin of the QTP, including ice–water phase transitions, heat exchange, mass transport, and the parameterized exchange of heat between the active layer and air. Based on the calibrated hydro-thermal model and combined with the electrical resistivity tomography survey and sample analysis results, a method for estimating the melting of ground ice was proposed. Simulation results indicate that the model effectively reflects the factual hydro-thermal regime of the RTS and can evaluate the ground ice ablation and total suspended sediment variation, represented by turbidity. Between 2011 and 2021, the maximum simulated ground ice ablation was in 2016 within the slump region, amounting to a total of 492 m3, and it induced the reciprocal evolution, especially in the headwall of the RTS. High ponding depression water turbidity values of 28 and 49 occurred in the thawing season in 2021. The simulated ground ice ablation and turbidity events were highly correlated with climatic warming and wetting. The results offer a valuable approach to assessing the effects of RTS on infrastructure and the environment, especially in the context of a changing climate.